1999
DOI: 10.1097/00126334-199907010-00008
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Guidelines for Antiretroviral Therapy and for Preventing Opportunistic Infections in HIV-Infected Adults and Adolescents in Ryan White–Funded Facilities in the United States

Abstract: To determine adherence by health care providers to guidelines for antiretroviral therapy and for prevention of opportunistic infections (OIs) in adults with HIV infection in federally funded facilities in the United States, we reviewed records of HIV-infected adults (>13 years) in 11 Ryan White Title III facilities in four states for information on eight standard-of-care recommendations during November 1996 through September 1997. Eligibility required a visit to the facility within 6 months before record abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 7 publications
2
21
1
3
Order By: Relevance
“…In the United States, 19% of a population-based sample of HIV-infected women had not had a Pap-test in the last 12 months, 8 while lack of lifetime Pap-smear was reported in 12% of another group of HIV-infected women. 9 In Italy, Zanetta and colleagues 10 observed that only 1 out of 6 HIV-infected women with ICC received a Pap-smear in the last 24 months and none in the last 12 months. In women of the general population, knowledge about Pap test was shown to be associated with increased use of screening, 11 whereas a low educational level was identified as a risk factor for lack of Pap-test knowledge.…”
mentioning
confidence: 99%
“…In the United States, 19% of a population-based sample of HIV-infected women had not had a Pap-test in the last 12 months, 8 while lack of lifetime Pap-smear was reported in 12% of another group of HIV-infected women. 9 In Italy, Zanetta and colleagues 10 observed that only 1 out of 6 HIV-infected women with ICC received a Pap-smear in the last 24 months and none in the last 12 months. In women of the general population, knowledge about Pap test was shown to be associated with increased use of screening, 11 whereas a low educational level was identified as a risk factor for lack of Pap-test knowledge.…”
mentioning
confidence: 99%
“…For example, 1 study reported a 70% vaccination rate for 1411 patients enrolled in 4 states (Maryland, Illinois, New York, and Georgia) under the US Health Resources and Services Administration's Ryan White Title III system. 8 However, these vaccination rates may not be reflective of all Ryan White Title III system clinics, as patients were limited to those seen within the past 6 months and only from study sites with expressed interest in study participation. The Veterans Aging (VA) Cohort 5-Site Study, which aimed to evaluate the impact of PPV23 on the incidence of pneumonia, evaluated vaccination status for 1626 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, our data show that uptake of the second PPV23 dose is much lower than the first dose, and there are no published studies evaluating uptake of the second PPV23 dose in HIV-infected patients. A recent study highlighted the potential benefit of PPV23 revaccination by demonstrating a significant rise in OPT above previously used vaccine response threshold (8) in HIV-infected patients revaccinated with PPV23 after 5 years. 21 As a result, the USAF program is conducting quality improvement initiatives, including in-services to educate providers, nursing chart review, and display of immunization schedules in patient examination rooms.…”
Section: Discussionmentioning
confidence: 99%
“…The most common technique used to study clinician adherence was a descriptive study that used a cross-sectional or retrospective chart review to measure adherence with practice guideline recommendations. [22][23][24][25][26][27] Another method used was the before-and-after observational study design with or without a concurrent control group. 19,28 In these studies, clinician adherence was measured by documentation in the clinical data base before and after implementation of an intervention designed to promote guideline adherence.…”
Section: Clinician Adherencementioning
confidence: 99%